2018
DOI: 10.7567/jjap.57.032701
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into generation of bursts of linearly-polarized, dissipative soliton pulses from a figure-eight fiber laser at 1.03 µm

Abstract: We experimentally demonstrate a simple and stable all-polarization maintaining fiber (PMF) nonlinear amplifying loop mirror (NALM)-based burst pulse fiber laser with a pulse number tuning capability, which can readily generate bursts of linearly-polarized femtosecond pulses at 1030 nm. The laser was based on an NALM that was operated to produce burst-mode, dissipative soliton pulses at a wavelength of 1030 nm, and these were then compressed into 400 fs Gaussian pulses using a grating pair-based compressor. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…However, it should be noted that the SA platform of SESAM was different from that of SnSe SA. The high‐speed oscilloscopic analysis (16 GHz digital signal analyzer, Tektronix) clearly showed that it was a single pulse, not a bunch of pulses which have often occurred in passively mode‐locked femtosecond pulse lasers, indicating that high‐quality femtosecond pulses were generated using our SnSe‐based laser system (Figure S6, Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that the SA platform of SESAM was different from that of SnSe SA. The high‐speed oscilloscopic analysis (16 GHz digital signal analyzer, Tektronix) clearly showed that it was a single pulse, not a bunch of pulses which have often occurred in passively mode‐locked femtosecond pulse lasers, indicating that high‐quality femtosecond pulses were generated using our SnSe‐based laser system (Figure S6, Supporting Information) …”
Section: Resultsmentioning
confidence: 99%
“…The burst pulse was generated in an ytterbium-doped double-clad fiber (YDF) using a small length of samarium-doped fiber as a saturable absorber [13]. The burst pulse output was obtained in allpolarization maintaining ytterbium-doped fiber using nonlinear amplifying loop mirror with the figure-eight configuration [14]. The burst pulse is generated through multimodal interference in a passively mode-locked ytterbium fiber-ring laser [15] or through an AOM-based harmonic mode-locking in a allnormal dispersion ytterbium fiber [16].…”
Section: Introductionmentioning
confidence: 99%
“…The traditional controlling technologies are mainly based on electricity, mechanics or magnetism [1][2][3], which are technically mature and stable but sensitive to electromagnetic interference and lace of compactness. As a neotype technology, the all-optical controlling technology has been widely studied due to its small volume, immunity to electromagnetic interference and compatibility with optical networks [4][5][6][7][8][9][10][11][12][13]. At 2016, Schnack et al realized all-optical control through intermodal phase difference, which has a potential application to all-optical switches [9], and an all-optical switch has been demonstrated [10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, all-fiber optical controlling systems has attracted considerable interest and become the research focus for their have numerous advantages, such as high reliability, easy access to all-optical network, immunity to electromagnetic interference [12][13][14]. A silica-based tunable all-fiber femtosecond laser system has been realized [15].…”
Section: Introductionmentioning
confidence: 99%